Persistent Collaboration: Between International and Indonesian National Law on the Utilization of Earth Orbit - Alfathimy, Deden Habibi Ali; Ardes, Runggu Prilia (UI Scholars Hub, 2025)
This paper examines the legal issues surrounding the utilization of Earth orbit as a valuable and finite resource for Indonesia and other countries by exploring the monism-dualism debate in the context space law discourse in Indonesia. The study starts with the discussions on monism and dualism in Earth orbit regulations. Then, the article explains relevant legal matters on space activities and the varying stances of some States before subsequently discusses legal divergences in Indonesia. The analysis of the article discloses both consistency and inconsistency between Indonesian national and international space law. The findings of this paper reveal that under the framework of monism, Indonesia can contribute to conforming State practices in international legal matters related to space activities through persistent collaboration as opposed to both persistent objection and acquiescence.